2013
DOI: 10.1097/rct.0b013e31829e0164
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Virtual Monochromatic Spectral Imaging for the Metallic Artifact and the Pulmonary Nodule Detection

Abstract: High monochromatic energy images can reduce metal artifacts without a change in nodule detection score. Low monochromatic energy images increase metal artifacts and worsen nodule detection in thick slices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…However, the suitable energy level of VMI for each situation is different. Gyobu et al (6) reported that metallic artifact significantly decreased in VMI at 100 keV or 140 keV and that VMI improved the detection of pulmonary nodules in a thoracic phantom study. Liu et al (7) reported that VMI at 74 keV with a metal artifact reduction algorithm could improve image quality for the micro-coil localization of pulmonary nodules.…”
Section: Artifact and Noise Reductionmentioning
confidence: 99%
“…However, the suitable energy level of VMI for each situation is different. Gyobu et al (6) reported that metallic artifact significantly decreased in VMI at 100 keV or 140 keV and that VMI improved the detection of pulmonary nodules in a thoracic phantom study. Liu et al (7) reported that VMI at 74 keV with a metal artifact reduction algorithm could improve image quality for the micro-coil localization of pulmonary nodules.…”
Section: Artifact and Noise Reductionmentioning
confidence: 99%
“…Virtual monoenergetic datasets of chest DECTs can be used to retrospectively increase the contrast-to-noise ratio within the thoracic vessels e.g., in case of low-keV reconstructions to confirm diagnosis of an incidental PE, a common finding in tumor patients [26][27][28]. Reasons to reconstruct high-keV virtual monoenergetic datasets are the decrease of metal artifacts from spine or shoulder implants that might limit the diagnostic accuracy in chest CT datasets [29,30].…”
Section: Dect Techniquementioning
confidence: 99%